Precise delineation and tumor localization based on novel image registration strategy between optical coherence tomography and computed tomography in the radiotherapy of intraocular cancer. (12th June 2019) - Gong, Changfei; Shen, Meixiao; Zheng, Xiaomin; Han, Ce; Zhou, Yongqiang; Xie, Congying; Jin, Xiance
Abstract: Radiation-associated toxicities due to sophisticated ocular anatomy and shape variability of organs at risk (OARs) are major concerns during external beam radiation therapy (EBRT) of patients with intraocular cancer. A novel two-step image registration strategy between optical coherence tomography (OCT) and computed tomography (CT) images was proposed and validated to precisely localize the target in the EBRT of patients with intraocular cancer. Specifically, multiple features from OCT and CT images were extracted automatically, then spatial transformation based on thin-plate spline function was performed iteratively to achieve feature alignment between the CT and OCT images. Finally, an exclusive OR (XOR) algorithm was applied for precise 3D registration using a 3D-mesh model generated from OCT and CT volumes. The accuracy of the proposed novel registration strategy was validated and tested in a schematic-eye phantom with an artificially introduced tumor and in ten patients with confirmed primary and/or secondary intraocular cancer. There was an average registration error and computational time of 0.21 ± 0.05° and 259 ± 5 s, together with an average Dice similarity coefficient and Hausdorff distance of 88.4 ± 0.65 and 0.89 ± 0.09, respectively. The preliminary experimental results demonstrated that the proposed novel strategy to overcome current limitations on eye modeling and to localize precisely the tumor target during EBRT of intraocular cancer is promising.